(untitled) (AYUSHDHARA, 2024)
The destruction/ break/ rupture/ discontinuity of body/tissue/ part of body is called “Vrana”. The definition of Granthi is very well described by Acharya Vagbhata and Acharya Sushruta which seems to be more or less the same. According to Vagbhata, Malas (Doshas) of which Kapha being predominant, vitiating the Medas (fat), Mamsa (muscle) and Asra (blood) gets localised in these tissues and produce a round elevated growth, compact in nature which is called Granthi. Acharya Sushruta has explained that “the scars of a wound never disappear even after complete healing and its imprint persists lifelong and it is called Vrana. This phenomenon of Vrana is not only limited to cutaneous lesion but may also extend upto muscles blood vessels, ligaments, bones, joints, visceral organs and other vital parts of body. According to Sushruta, Granthi is a Vrita (round), Unnata (elevated), Vigrathita (hard) swelling by pathological involvement of Mansa, Rakta and Meda. Modern science compares Vranagranthi to keloid. It is a tumour arising from fibro proliferative disorders of the dermis. The main phenomenon is the excessive deposition of extracellular matrix proteins, which is composed by collagen fibres. It develops exclusively in humans. There is no proven, efficient treatment for keloid. This case study will lead to the development of new and improved keloid treatment methods.